2017
DOI: 10.1088/1751-8121/aa54d9
|View full text |Cite|
|
Sign up to set email alerts
|

Approximation and inference methods for stochastic biochemical kinetics—a tutorial review

Abstract: Stochastic fluctuations of molecule numbers are ubiquitous in biological systems. Important examples include gene expression and enzymatic processes in living cells. Such systems are typically modelled as chemical reaction networks whose dynamics are governed by the Chemical Master Equation. Despite its simple structure, no analytic solutions to the Chemical Master Equation are known for most systems. Moreover, stochastic simulations are computationally expensive, making systematic analysis and statistical inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
422
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(425 citation statements)
references
References 266 publications
3
422
0
Order By: Relevance
“…where ( , ) was the probability density of protein concentration y. Next, the chemica l master equation was transformed into the Fokker-Planck equation [12,21,49,[65][66][67]:…”
Section: Stochastic Potential and Probability Density Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…where ( , ) was the probability density of protein concentration y. Next, the chemica l master equation was transformed into the Fokker-Planck equation [12,21,49,[65][66][67]:…”
Section: Stochastic Potential and Probability Density Functionmentioning
confidence: 99%
“…Recent examples of opposing behavior further highlight the importance of considering the contribution of stochasticity to cellular circuitry. On the one hand, it has been shown that noise can induce multimodality and even stochastic memory in a system that, according to a deterministic description, lacks bistability [48,49]. On the other hand, stochastic fluctuations in gene expression levels often reduce or disrupt the memory function of biological networks [21,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, however, explicit solutions are unavailable or intractable and one resorts to stochastic simulation or seeks a numerical solution to a finite truncation of the master equation (Munsky and Khammash, 2006;Borri et al, 2016;Gupta et al, 2017). An alternative approach, which often provides useful qualitative insights into the model behaviour, is based on reduction techniques such as quasi-steadystate (Srivastava et al, 2011;Kim et al, 2014) and adiabatic reductions (Bruna et al, 2014;Popovic et al, 2016), piecewise-deterministic framework (Lin and Doering, 2016;Lin and Buchler, 2018), linear-noise approximation (Schnoerr et al, 2017;Modi et al, 2018), or moment closure (Singh and Hespanha, 2007;Andreychenko et al, 2017;Gast et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…1). These networks can be modeled using the chemical master equation: a set of differential equations describing the state probabilities and connected transition rates for each state (15). Biochemical networks are generally Markovian (16), have a number of different control patterns (17), and typically adhere to specific design principles (18).…”
Section: Introductionmentioning
confidence: 99%